Supervision Strategy of the Business Competition Supervisory Commission on Anti-Competition Practices - Humairah, Nabila; Siregar, Taufik; Isnaini, Isnaini (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to examine the supervision strategy carried out by the Business Competition Supervisory Commission (ICC) against anti-competition practices that can harm the market and consumers. ICC has a very important role in maintaining healthy business competition through supervision, law enforcement, and policy recommendations. This study uses a qualitative approach with in-depth interview methods and document analysis related to the implementation of the business competition law. The results of the study show that ICC carries out supervision through a preventive, detective, and law enforcement approach. Preventive supervision is carried out through education to business actors, while detective supervision utilizes technology such as big data to detect anti-competitive practices. Although the law enforcement carried out by ICC has succeeded in cracking down on many violations, it is constrained by a deterrent effect that is still low due to the amount of sanctions that are not proportional to the profits obtained from these illegal practices. In addition, ICC also functions as a policy advisor to encourage the creation of regulations that support fair business competition. This research suggests the need to increase the capacity of technology and human resources, as well as revisions to the amount of sanctions so that they can be more effective in tackling anti-competitive practices in Indonesia.